An In vitro study to evaluate the efficacy of Dentinal tubule penetration of two types of root canal filling material: AH plus and Bio-ceramic HIFlow (Journal of Hama University, 2022)
Endodontic treatment is one of the complex treatments in the world of dentistry, which requires a lot of scientific and practical experience of practitioners and specialists, and with great technical progress, there are many treatment methods, so that this study aims to measure the ability of the Bio-ceramic HI Flow paste to be inserted into the dentinal tubule and compare it with AH Plus, the sample consisting of 40 single-root lower pre-molars was collected and divided into two groups of 20 pre-molars for each group, in the first group the AH PLUS paste was used, in the second group the Bio-ceramic HI flow paste was used, in both groups the single cone was used for the filling To independently study the properties of each paste without the influence of the filling method.Wait 24 hours until the solidification is complete and then longitudinal sections were made and the depth of insertion was measured at a distance of 3 mm (the apical third) and at a distance of 6 mm (the middle third) using a light transmitting microscope. Statistically significant differences were observed when applying the T- Student test for independent samples when Comparison of insertion results in longitudinal sections in the middle trimester P = 0.00 and in the peak third P = 0.00. Between the two study groups, Ah plus achieved better insertion of Bio ceramic HI flow paste into the dentinal tubules, which contributes to better sealing within the dentinal tubules.
Keywords: Dentinal tubule - bio ceramic HI flow - ah plus